FORMALIZATION OF LOCOMOTIVE DRIVER ACTIVITY TENSION INDICATOR BASED ON THE ERGONOMIC MODEL - Horobchenko, O. M.; Antonovych, A. O. (Science and Transport Progress, 2017)
Purpose. A key factor contributing to the safety and quality of ergatic system "train-driver" is the intensity of the locomotive crew’s work. The aim of this work is formalization of locomotive driver activity tension indicator. Methodology. One of the characteristics of driver activity tension is the difference between the time allotted to complete the task, and the necessary (external reserve or deficiency time). The sets of major and minor operations in the management of the train locomotive in different train situations were identified. Using the methods of fuzzy logic, the concept of "materiality of the operation of the locomotive control" is presented in the form of a set of linguistic variables. To determine the function membership of the elements of the set "the importance of the operation of the locomotive control" the method of expert evaluations was used. Coefficient of temporary tension is presented in the form of fuzzy number L-R-type. Findings. It was found the value of the relative number of operations of locomotive control according to the distribution using the parameter of operation "importance". To determine the most tensioned mode of the driver ranking the traffic condition according to the parameter of relative amounts of the important management operations was conducted. The most difficult modes are the "front hindrance", "movement in unfavorable weather conditions" and "departure from the station to the running line". Originality. The introduction of the value "conventional importance of the operation" allowed us to more accurately describe the terms of train driving. For the first time the work presents determination of tension of the driver’s work in the form of a unimodal fuzzy number, which will make it possible to use the methods of the theory of artificial intelligence to simulate activity of the locomotive driver and develop intelligent control systems. Practical value. There were obtained the opportunity to consider such an important quality indicator, as "the tension of the driver’s work" in systems of automatic train control and traffic safety. Ranking the onboard situations and control operations enables us to justify the order of management action for the improvement of the algorithms of system operation of train driving.